76 WHOLE-EXOME SEQUENCING EXPLORES DIFFERENTIAL GENES EXPRESSION OF METASTASIS IN ESOPHAGEAL SQUAMOUS CELL CARCINOMA: A PROPENSITY-SCORE MATCHING STUDY. (14th September 2020) - Zeng, Y; Liu, M; Xiang, C; Yu, J; Han, Y; Li, Z; Fu, X; Cai, X
Abstract:  : Metastasis is the most popular failure pattern for esophageal squamous cell carcinoma (ESCC) patients. There were rare ESCC patients with stage T1-3N0M0 metastasized within 1 year after surgery or stage T1bN3M0, while many ESCC patients with stage T1-3N0M0 didn't metastasize within 2 years after surgery or stage T1bN0M0. This study is to analyze paired ESCC patients with or without early distant metastasis or multiple lymph nodes, and identify potential biomarkers for early metastasis of ESCC. Methods: 1942 ESCC patients who underwent surgery in our institution were retrospectively reviewed from January 2013 to December 2017. One group of patients with stage T1-3N0 who developed metastasis within one year and without recurrence within two years after surgery (M group), and another group of patients with stage T1bN0 and T1bN3 (N group) were screened. We matched patients with the critically clinicopathological factors by propensity-score matching (PSM) method. Whole-exome sequencing (WES) was performed on the formalin-fixed paraffin embedded samples of the included patients. Statistical analysis was performed by SPSS version 22.0. Results: From 1942 patients screened, there were only 6 T1-3N0 patients with early distant metastases and 4 T1bN3 patients. We paired 6 T1-3N0 patients without recurrence within two years and 4 T1bN0 patients by PSM. The median overall survival (mOS) of patients in M1 was 21 months, while M0 did not reached. The mOS of patients in N3 and N0 were 10 months and 48 months, respectively. The WES result showed that the FRG1, HLA-DRB1 and MUC6 expressed differentially in these patients. However, only the HLA-DRB1 expression was associated with the survival of patients in N group by univariate analysis (p = 0.013). Conclusion: Regardless of the small sample size, the study identified several genes correlated with the early metastasis of ESCC. ESCC patients with T1bN3M0 had significantly higher expression of HLA-DRB1 gene than patients with T1bN0M0 (p = 0.013). It seemed that HLA-DRB1 gene was correlate with early multiple lymph nodes metastases, which needs further research and may be helpful in new drug discovery.